Studying the portrait of a volunteer on the example of a volunteer on the example of Kazakh student youth - Каримова, Р.; Фомина, Татьяна (Pedagogy and Psychology, 2022)
This article includes a study of the study of the portrait of a modern volunteer on the example of Kazakh student youth. The principles on which volunteering is based, methods of theoretical analysis of literary sources are considered, valuable recommendations are given on the portrait of modern student youth according to which it is possible to conduct a qualitative selection of fighters in the ranks of volunteer student youth. Therefore, the relevance of this study was solved by the transformations in the education system in our Kazakh society in a state of cooperation of national traditions, rapid socio-economic changes that decide the social situation in the development of youth.